2010
DOI: 10.1089/neu.2009.1162
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating Experimental Spinal Cord Injury by Hyperbaric Oxygen: Stimulating Production of Vasculoendothelial and Glial Cell Line-Derived Neurotrophic Growth Factors and Interleukin-10

Abstract: The present study was carried out to further examine the mechanisms underlying the beneficial effects of hyperbaric oxygen (HBO(2)) on experimental spinal cord injury (SCI). Rats were divided into three major groups: (1) sham operation (laminectomy only); (2) laminectomy + SCI + normobaric air (NBA; 21% oxygen at 1 ATA); and (3) laminectomy + SCI + HBO(2) (100% oxygen at 2.5 ATA for 2 h). Spinal cord injury was induced by compressing the spinal cord for 1 min with an aneurysm clip calibrated to a closing press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 32 publications
0
27
0
2
Order By: Relevance
“…Rats with compression spinal cord injury treated with HBOT immediately after the insult had smaller spinal cord infarction, less apoptosis, decreased spinal cord production of interleukin-1beta and tumour necrosis factor-alpha, lower expression of HIF-1alpha and higher production of interleukin-10 and vasculo-endothelial and glial cell line-derived neurotrophic growth factors in comparison with untreated controls [18][19][20]. These findings correlated with the better motor function scores in the HBOT treated animals [18,19].…”
Section: Discussionmentioning
confidence: 93%
“…Rats with compression spinal cord injury treated with HBOT immediately after the insult had smaller spinal cord infarction, less apoptosis, decreased spinal cord production of interleukin-1beta and tumour necrosis factor-alpha, lower expression of HIF-1alpha and higher production of interleukin-10 and vasculo-endothelial and glial cell line-derived neurotrophic growth factors in comparison with untreated controls [18][19][20]. These findings correlated with the better motor function scores in the HBOT treated animals [18,19].…”
Section: Discussionmentioning
confidence: 93%
“…Many studies have used terminal deoxynucleotidyl transferase (TdT) dUTP nick-end labeling (TUNEL) staining to show that HBO therapy significantly reduces apoptosis in injured spinal cord tissue, and most of the studies have proposed potential pathways by which HBO therapy attenuates apoptotic cell death after SCI 1519202327303133…”
Section: Experimental Studies: Potential Mechanisms Of Hbo Neuroprotementioning
confidence: 99%
“…Numerous studies have shown that HBO significantly improves the levels of BDNF, GDNF and NGF in ischemic injury. Simultaneously, studies have shown that the positive effects still exist in brain damage [75] and spinal cord injury [76] . Long-course and repeated HBO therapy for cerebral ischemia can also generate similar outcomes [52,77] .…”
Section: Hbo Inhibits Apoptosis and Neuroprotective Effectsmentioning
confidence: 99%